Efficacy and Safety of Ultrasound Guided-Deep Serratus Anterior Plane Blockade With Different Doses of Dexmedetomidine for Women Undergoing Modified Radical Mastectomy: A Randomized Controlled Trial - Xu, Xia; Chen, Xingfang; Zhu, Wenchao; Zhao, Jing; Liu, Yanchao; Duan, Caiping; Qi, Yingying (Frontiers in Medicine, 2022)
Background: Ultrasound guided-deep serratus anterior plane block (USG-DSAPB) has been used for pain management of patients undergoing modified radical mastectomy (MRM), but evidence supporting their adjuvant analgesic benefits is limited. We explored the efficacy and safety of preemptive use of ropivacaine combined with different doses of dexmedetomidine (DEX) in USG-DSAPB for patients undergoing MRM. Methods: Ninety-five female patients undergoing unilateral MRM were allocated randomly to two groups. The primary outcome was sufentanil consumption 72 h after USG-DSAPB. Secondary outcomes were: postoperative pain scores and level of sedation; intraoperative hemodynamics; duration of post-anesthesia care unit (PACU) stay; prevalence of moderate-to-severe pain; one-time puncture success; procedure time of blockade; time to first rescue analgesia; requirement of rescue analgesia; satisfaction scores of patients and surgeons; duration of hospital stay; adverse events; prevalence of chronic pain; quality of postoperative functional recovery. Results: Compared with the RD1 group, the visual analog scale score for coughing was significantly lower at 4, 8, 12 h and sufentanil consumption was significantly lower at 4, 8, 12, 24, 48 h after surgery in the RD2 group (P < 0.05). The time to first rescue analgesia was significantly longer in the RD2 group (P < 0.05). The requirement for rescue analgesia was significantly higher in the RD1 group (P < 0.05). The prevalence of moderate-to-severe pain, number of patients using vasoactive agents, duration of PACU stay, as well as consumption of propofol, remifentanil, and DEX were significantly lower in the RD2 group (P < 0.05). There were no significant diﬀerences between the two groups with respect to one-time puncture success, procedure time of blockade, total dermatomal spread, satisfaction scores of patients and surgeons, postoperative complications, duration of hospital stay, 40-item Quality of Recovery questionnaire (QoR-40) score, or prevalence of chronic pain (P > 0.05). Conclusions: We discovered that 1 μg·kg–1 (not 0.5 μg·kg–1) DEX combined with 20 mL of 0.5% ropivacaine and 5 mg of dexamethasone in USG-DSAPB could provide superior postoperative analgesia for patients undergoing MRM. However, the quality of postoperative functional recovery and prevalence of chronic pain were similar.